PENGEMBANGAN MODEL PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN DAYA SAING LULUSAN PESERTA KURSUS DI MAHESA INSTITUTE PARE KEDIRI JAWA TIMUR - Taufik Hidayat; Siti Nurhalimah (Ilma Jurnal Pendidikan Islam, 2022)
Not a few institutions that are able to print the birth of proficient graduates. For example, non-formal institutions that have seen the results of their students. Increasingly stringent competitiveness makes each institution always fix and evaluate their institution. For the sake of creating graduates who have good and great competitiveness so that they are worthy to compete in this global world. This study aims to obtain information on how to develop interactive learning models in increasing the competitiveness of course participants at Mahesa Institute Pare, Kediri, East Java. This study used qualitative research methods. Qualitative research is an approach that is also called an investigative approach because researchers usually collect data by means of face-to-face and interacting with people in the research place (Mc Millan & Schumacher, 2003). This study aims to research and find as much information as possible from a phenomenon. Theorizations and hypotheses in this type of research are not needed. To obtain adequate information about this research, literature review and field observations are conducted by conducting interviews. The location of this research was conducted at the Mahesa Institute in Pare Kediri, East Java. The results of observations and interviews are that there is interactive learning to increase the competitiveness of Mahesa Institute graduates to be able to develop talents and knowledge that graduates can acquire after a course at Mahesa Institute Pare, Kediri, East Java. From the results of this study, it can be concluded that interactive learning is very much needed to improve the competitiveness of participants who graduate from Mahesa Institute.